Digital Storytelling for Inclusive Education: Voices of Students with Special Needs in the Classroom - Ni Wayan Karmini; Nong Chai; Siri Lek; Rustiyana Rustiyana (International Journal of Educational Narratives, 2025)
Background. The integration of digital storytelling in inclusive education offers new possibilities for amplifying the voices and experiences of students with special needs. This study investigates how digital storytelling functions as a medium of expression, participation, and empowerment in inclusive classroom environments. Purpose. The research aims to explore how students with diverse learning abilities use digital narratives to communicate their perspectives, develop self-confidence, and engage collaboratively with peers. Method. A qualitative case study design was employed, involving 20 students with special needs and 5 inclusive education teachers across three schools. Data were collected through classroom observations, interviews, and analysis of student-created digital stories. Results. Thematic analysis revealed that digital storytelling enhanced students’ sense of agency and belonging by enabling them to represent their identities through multimodal expression combining voice, images, and text. Teachers reported that storytelling projects fostered empathy, cooperation, and deeper understanding among all students. Conclusion. The study concludes that digital storytelling provides an inclusive pedagogical approach that bridges cognitive, emotional, and social learning, promoting equitable participation and self-advocacy for students with special needs in mainstream education.